Starting Conditions of Multi-Stakeholder Collaboration in Developing the “Makassar Kota Makan Enak” City Branding : JEL Classification: Z32, Z38, H83, L83, M31 - Muh. Taufik; Badu Ahmad; Muh. Akmal Ibrahim; Nurdin Nara (Journal La Bisecoman, 2026)
This study examines the dynamics of collaborative governance in the development of culinary tourism in Makassar City, Indonesia, within the framework of public administration. Grounded in a qualitative case study approach, data were collected through interviews, observation, and documentation involving key stakeholders, including government agencies, culinary MSMEs, communities, and digital platform partners. The findings reveal that the “Makassar, the City of Delicious Food” initiative emerged as a strategic response to post-pandemic economic recovery, leveraging local culinary potential as both a cultural asset and economic driver. Collaboration is characterized by strong interdependence among actors, where government functions as facilitator, MSMEs as economic drivers, and digital platforms as market enablers. Initial trust and social capital, built through prior informal collaborations, significantly support the governance process, although challenges such as resource inequality, inconsistent program implementation, and limited evaluation mechanisms persist. The study also highlights a transition from hierarchical governance toward network-based governance, emphasizing participatory decision-making and adaptive learning. Overall, Makassar’s experience reflects an emerging collaborative governance model that contributes to public value creation, while requiring further institutional strengthening to ensure sustainability and equity.